Functional and Structural Neural Changes in Obsessive-compulsive Disorder after Pharmacotherapy - Atmaca, Murad (Bentham Science Publ Ltd, 2019)
Obsessive-compulsive disorder (OCD) is an important disorder which is disturbing the quality of life and is characterized by repetitive thoughts and behaviors, now in a different category in the Diagnostic and Statistical Manual for Mental Disorders Fifth Edition (DSM 5). Neuroimaging investigations are very useful to reveal a neurobiological model of the OCD. Studies conducted in the last quarter century have shown clear results and revealed that specific cortico-subcortical circuits could be involved in the occurrence of OCD symptomatology. These neuroimaging studies pointed out some important findings for OCD patients. Our present information implicates some problems in some cortico-subcortical in the pathophysiology of OCD. In the present paper, final information on the neuroanatomy and neurochemistry of OCD was reviewed, revising the effects of anti-obsessional drugs on the structural and functional neuroimaging studies. As can be seen in the review, drug treatments can generally affect the brain structurally and functionally, suggesting that brain of OCD tends to neuroplasticity. However, it is not clear that these effects of pharmacotherapy are related to anti-obsessional drugs per se or impact on the improvement of the disorder.
Keywords: OCD; functional; structural; pharmacotherapy; neural; changes